A MODEL OF FAMILY AND CAREER RECONCILIATION - Tandzegolskienė, Ilona; Trepulė, Elena; Rutkienė, Aušra; Tamoliūnė, Giedrė; Jurgilė, Vaida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article focuses at these elements of family, work and career reconciliation which are relevant for seeking harmony and satisfaction in family and work settings. Presented theme refers to the analysis of work-family or family-work conflict, causes for role conflicts, facilitation strategies, conception of dual and individual career within a family, internal and external factors which influence start-up of conflicts and reconciliation strategies. This article presents results of data, collected during conduction of narrative interviews with young parents (both mother and father), semi-structured interviews with employers, focus group with career guide/human resources specialists and quantitative research with young families. The aim of research was to determine the needs and opportunities of young families who seek to balance family and career by highlighting influence of work activities. Research results identicated reconciliation for young families and career, possibilities for facilitation that is closely linked to dual and single career design couples, trends for career development, aware ness of parent hood and changing roles.